Suicidal risks and coping strategies of student personnel assistants in a southern Philippine college - Daryl B. Casamorin; Henry E. Lemana II; Sherry V. Mecida; Cathy D. Calong; Angelica S. Padilla; Bria Ysabela O. Santiago; John Lloyd B. Mestidio; Kenn N. Tulod; Michael E. Ganayo III; Paloma B. Ladrido; Ralf Vincent P. Bagual (Northern Negros State College of Science and Technology (NONESCOST), 2023)
In addition to their formal education, many students often work to supplement their income, gain valuable experience, and keep themselves motivated. However, behind the forces to become working students and the benefits they can acquire from being such, drawbacks like burnout that may lead to suicidal ideation inevitably confront them. This study was aimed at determining the suicidal risks and coping strategies, both negative and positive, of the student personnel assistants (SPAs) in one tertiary institution in the Philippines. This study employed a descriptive-correlational methodology, in which the researchers utilized complete enumeration to cover twenty-nine (29) SPAs as respondents of the study. An adopted survey questionnaire was used as an instrument and was distributed to the respondents through Google forms. After gathering the data, the results revealed that SPAs have a mild suicidal risk. They apply positive coping strategies more than negative ones. Further, family monthly income was the primary predictor of suicidal risks among SPAs. Lastly, results show that there is a significant relationship between suicidal risks and positive and negative coping strategies, which implies that the lower the suicidal risks, the higher the positive coping strategies, and vice versa. Based on the results of the study, the researchers recommend that SPAs should apply positive coping strategies more to prevent severe suicidal risks, teachers must be aware of the mental health status of students and reinforce them positively during the teaching-learning process, parents of SPAs must find ways to holistically support their children to prevent them from having mental health issues that could lead to suicidal risks, guidance counselors must intensify their mental health programs and services to prevent suicidal risks, school administrators should continue supporting SPAs, and future researchers should explore more aspects of suicidal concerns that affect students in the next normal.